Fire Tongues- Woman of Fire Three Day Celebration (2025)
A flyer for Fire Tongues Woman of Fire three day celebration taking place in Santa Monica for January 21-23 1994. Michele Serros attended Pachanga de Palabra January 22nd 1994.